Pengaruh Model Pembelajaran Discovery-Inquiry terhadap Peningkatkan Kemampuan Berpikir Kreatif Materi Fisika pada Siswa SMA - Kholasatun Nurul Fatmasari; Kamaluddin Kamaluddin; Muhammad Ali (Jurnal Kreatif Online, 2021)
The purpose of the study was to determine the effect of the Discovery-Inquiry learning model on improving the senior high school students' creative thinking skills in material of physics. The study was pre-experimental. The research design was a one-group pretest-posttest design. The sample was selected by purposive sampling. The sample in this study was class X MIPA 1 SMA Negeri 5 Palu as the experimental group. The average pretest score in this study was 11.27 and the average posttest score was 14.40 out of a total score of 24. The results of the N-gain calculation were 36.5%. It shows that the N-gain value is in the medium category. The results of hypothesis testing show that the value of tcount = 18.57 > ttable = 1.69 so that H0 is rejected and H1 is accepted. Thus, it can be concluded that there is an effect of the Discovery-Inquiry learning model on improving senior high school students' creative thinking skills in material of physics.